Satire on The Meme “Nurhadi-Aldo” As a Social Critique of Society - Fauzi, Aziz; Suta Wardianto, Bayu; Hayati, Rifa’atussalwa; Kemala (International Proceedings of Nusantara Raya, 2022)
The research discusses the Nurhadi-Alo meme with a stylistic approach, especially in three figures of speech, namely irony, sarcasm, and parody. The method used in this research is descriptive qualitative. In addition, the techniques for data use three techniques, namely: literature study techniques, observation techniques, note-taking techniques, and documentation techniques. The results of the study were 27 data which were included in satire. Satire can be classified into three figures of speech, namely irony, sarcasm and parody. Irony data found 2 (two) data, sarcasm data found 13 (thirteen) data, and parody data found 12 (twelve) data.